MANAJEMEN PEMBELAJARAN YOGA DALAM KEGIATAN EKSTRAKURIKULER SISWA HINDU DI SMPN 1 MATARAM - Sintia, Ni Kadek; Pramana, Ida Bagus Kade Yoga (Fakultas Dharma Acarya IAHN-TP Palangka Raya, 2025)
ABSTRACT Extracurricular activities are a form of support for character building, skills, and the development of students' potential, interests, and talents. To be able to achieve these goals, learning management needs to be carried out to ensure that learning activities can run systematically and achieve learning objectives. So this study aims to describe the learning management process of yoga in extracurricular activities of Hindu students at SMPN 1 Mataram. This research is a type of descriptive qualitative research with a phenomenological approach. Data collection in this study was carried out through participant observation, unstructured interviews, and documentation. Data analysis was carried out through three stages, namely data sorting, data presentation, and conclusion making. The results of this study indicate that yoga learning management in extracurricular activities of Hindu students at SMPN 1 Mataram is carried out through four main stages, namely planning, organizing, implementing, and evaluating. Each stage has different interrelationships and aspects. However, some of the obstacles faced are lack of knowledge regarding the importance of yoga, limited facilities, physical obstacles, time constraints, and unfavorable weather. Keywords: Learning Management, Yoga, Extracurricular Activities